2018
DOI: 10.1111/mec.14938
|View full text |Cite
|
Sign up to set email alerts
|

Holobiont suture zones: Parasite evidence across the European house mouse hybrid zone

Abstract: Parasite hybrid zones resulting from host secondary contact have never been described in nature although parasite hybridization is well known and secondary contact should affect them similarly to free‐living organisms. When host populations are isolated, diverge and recontact, intimate parasites (host specific, direct life cycle) carried during isolation will also meet and so may form parasite hybrid zones. If so, we hypothesize these should be narrower than the host’s hybrid zone as shorter parasite generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…Here, we summarize the few available examples of intraspecific genetic sampling of Pneumocystis from multiple localities across a host range. In two well-studied Pneumocystis species, the human-associated P. jirovecii and mouse (Mus musculus)-associated P. murina, variation has been observed at only two or three bases out of the approximately 250 bp long mtLSU fragment (0.8% to 1.2%) [19,20]. Pneumocystis sequences were recovered from populations of Mexican free-tailed bats (Tadarida brasiliensis) from Mexico and Argentina, with maximum divergence of 0.78% at mtLSU and 1.83% at mtSSU; in the common pipistrelle bat (Pipistrellus pipistrellus), no divergence was observed among individuals at mtLSU, but 0.49% divergence was seen at mtSSU [9].…”
Section: Expected Divergence At Pneumocystis Barcodesmentioning
confidence: 99%
“…Here, we summarize the few available examples of intraspecific genetic sampling of Pneumocystis from multiple localities across a host range. In two well-studied Pneumocystis species, the human-associated P. jirovecii and mouse (Mus musculus)-associated P. murina, variation has been observed at only two or three bases out of the approximately 250 bp long mtLSU fragment (0.8% to 1.2%) [19,20]. Pneumocystis sequences were recovered from populations of Mexican free-tailed bats (Tadarida brasiliensis) from Mexico and Argentina, with maximum divergence of 0.78% at mtLSU and 1.83% at mtSSU; in the common pipistrelle bat (Pipistrellus pipistrellus), no divergence was observed among individuals at mtLSU, but 0.49% divergence was seen at mtSSU [9].…”
Section: Expected Divergence At Pneumocystis Barcodesmentioning
confidence: 99%
“…Although several recent studies have described the existence of hybrid Pneumocystis using multiple genetic markers [27], isoenzymatic and first genetic data suggested that speciation in the Pneumocystis genus resulted from long genetic isolation and a potential co-speciation process [28,29]. The approximate time of Pneumocystis speciation was estimated by Keely et al [30], who examined the genetic variations at rRNA and DHFR loci between different Pneumocystis species.…”
Section: Pneumocystis Organisms As Stenoxenic Organisms With a Long Hmentioning
confidence: 99%
“…Although many studies have been devoted to comparing phylogenies and population structures of host–parasite associations, only a few analysed these processes within the context of host secondary contact zones and hybrid zones (reviewed by Theodosopoulos et al., 2019), and only recently, de Bellocq et al. (2018) focused on detecting a hybrid zone in parasite populations. Using two parasites of the house mouse Mus musculus , the nematode Syphacia obvelata and the fungus Pneumocystis murina , they found that within the host's hybrid zone both parasites create their own hybrid zone.…”
Section: Introductionmentioning
confidence: 99%